SEDLIN forms homodimers: characterisation of SEDLIN mutations and their interactions with transcription factors MBP1, PITX1 and SF1. - Jeshmi Jeyabalan; M Andrew Nesbit; Juris Galvanovskis; Richard Callaghan; Patrik Rorsman; Rajesh V Thakker (PLoS ONE)
Background SEDLIN, a 140 amino acid subunit of the Transport Protein Particle (TRAPP) complex, is ubiquitously expressed and interacts with the transcription factors c-myc promoter-binding protein 1 (MBP1), pituitary homeobox 1 (PITX1) and steroidogenic factor 1 (SF1). SEDLIN mutations cause X-linked spondyloepiphyseal dysplasia tarda (SEDT). Methodology/principal findings We investigated the effects of 4 missense (Asp47Tyr, Ser73Leu, Phe83Ser and Val130Asp) and the most C-terminal nonsense (Gln131Stop) SEDT-associated mutations on interactions with MBP1, PITX1 and SF1 by expression in COS7 cells. Wild-type SEDLIN was present in the cytoplasm and nucleus and interacted with MBP1, PITX1 and SF1; the SEDLIN mutations did not alter these subcellular localizations or the interactions. However, SEDLIN was found to homodimerize, and the formation of dimers between wild-type and mutant SEDLIN would mask a loss in these interactions. A mammalian SEDLIN null cell-line is not available, and the interactions between SEDLIN and the transcription factors were therefore investigated in yeast, which does not endogenously express SEDLIN. This revealed that all the SEDT mutations, except Asp47Tyr, lead to a loss of interaction with MBP1, PITX1 and SF1. Three-dimensional modelling studies of SEDLIN revealed that Asp47 resides on the surface whereas all the other mutant residues lie within the hydrophobic core of the protein, and hence are likely to affect the correct folding of SEDLIN and thereby disrupt protein-protein interactions. Conclusions/significance Our studies demonstrate that SEDLIN is present in the nucleus, forms homodimers and that SEDT-associated mutations cause a loss of interaction with the transcription factors MBP1, PITX1 and SF1.